New digital technologies, financialization, and the Covid-19 pandemic: changes in the global productivity dynamics, the role of the State, and impacts on HEIC - Cassiolato, José Eduardo; Falcón, Maria Lucia; Szapiro, Marina (Cadernos do Desenvolvimento, 2023)
This article analyzes the recent changes in the global productivity and innovation dynamics and its impacts on the industrial and innovation public policies since the beginning of the millennium. Arguably, the main feature that singles out the current state of globalization is the strengthening of the financialization process. This has had significant impacts on transnational firms and the outreach of National States’ actions. This article also discusses to what extent the Covid-19 pandemic is affecting the economy, the society, and the measures adopted by National States to face the current crisis. The role of new digital technologies in global changes, the industrial and innovation policies, especially in the health productivity and innovation system, are other discussion topics. Finally, this study highlights the structural changes in the global economy against the background of the Covid-19 pandemic and investigates the main challenges and opportunities for HEIC worldwide and in Brazil.